2018
DOI: 10.1111/nep.13201
|View full text |Cite
|
Sign up to set email alerts
|

Renal ultrasound and Doppler parameters as markers of renal function and histopathological damage in children with chronic kidney disease

Abstract: Any increase in the RI and PI values must arouse alarm to the possibility of advancing renal damage. Moreover, RI and PI could fairly predict the degree of glomerular sclerosis and interstitial fibrosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…Sawires et al have also suggested PI as one of the Doppler markers of renal dysfunction in children. They have shown a significant difference in PI (p = 0.02), amongst other tested parameters, when comparing a group of 42 children with chronic kidney disease (1.05 ± 0.36) with 42 healthy controls (0.89 ± 0.23) [44].…”
Section: Pulsatility Index In Childrenmentioning
confidence: 95%
“…Sawires et al have also suggested PI as one of the Doppler markers of renal dysfunction in children. They have shown a significant difference in PI (p = 0.02), amongst other tested parameters, when comparing a group of 42 children with chronic kidney disease (1.05 ± 0.36) with 42 healthy controls (0.89 ± 0.23) [44].…”
Section: Pulsatility Index In Childrenmentioning
confidence: 95%